Implementasi Model Pembelajaran Problem Based Learning (PBL) Tentang Materi Biologi Untuk Meningkatkan Keterampilan Pemecahan Masalah: Literature Review - Putri Silmi Nurul Fadila; Fitri Arsih; Ganda Hijrah Selaras; Heffi Alberida (Center for Research and Community Service (LPPM) University of Abulyatama, 2023)
Biology learning is prepared to encourage students to be able to solve problems in everyday life. To be able to realize this, a learning model is needed that can construct students' knowledge so that they are able to solve problems. This study aims to see how to implement the Problem Based Learning (PBL) learning model as an effort to improve students' problem solving skills in high school, especially in Biology learning. The method used in this research is literature review. The reading sources used are from relevant national and international articles. Data analysis techniques were carried out descriptively by analyzing and identifying reading sources so as to produce a concise, clear and informative summary. The results showed that the implementation of the PBL learning model could improve students' problem-solving skills, especially regarding biology material.